PENGARUH KEPUASAN DAN MOTIVASI KERJA TERHADAP KINERJA GURU HONORER DI SMA NEGERI 4 KERINCI - Sudirman . (Jurnal Ekonomi Sakti, 2020)
This study aims to determine the effect of satisfaction and work motivation on the performance of honorary teachers in high school 4 kerinci. The analytical tool used is multiple linear regression with the help of SPSS statistical sofware version 20. Techniques in sampling in this research was done with full sampling technique, as many as 37 respondents. Data collecting technique using questionnaire and literature. The hypothesis of this research is that there is a significant influence berween work satisfaction and motivation on the performance of honorary teachers in high school 4 kerinci. The results of the study show that the satisfaction variabel has a significant effect on honorary teacher performance with the prove t arithmetic > t table (4,728 > 2,03224) or sig < a (0,000 < 0,05) and work motivation variables have a significant effect on the performance of honorary teachers in high school 4 kerinci with proven t arithmetic > t table(3,056 > 2,03224) atau sig < a (0,004 < 0,05). The results of the F test indicate that the variables of satisfaction and motivation of work simultaneously influence the performance of honorary teachers in high school 4 kerinci with proven F arithmetic > F table (16,051 > 3,28) or sig < a (0,000 < 0,05). The amount of influence of satisfaction and work motivation on the performance of honorary teachers in high school 4 kerinci is 48,6% while the remaining 51,4% are explained by other causal factors not examined in this research.